PENERAPAN MODEL PROBLEM-BASED LEARNING (PBL) MELALUI MEDIA PEMBELAJARAN WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR MENGENAL PETA MATA PELAJARAN IPAS SISWA KELAS IV SDN BANJARSAWAH I - Rafika Maulidiah Karomah; Ribut Prastiwi Sriwijayanti; Didit Yulian Kasdriyanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This research was motivated by the low learning outcomes of fourth grade students at SDN Banjarsawah I in the IPAS subject on map recognition material. The low learning outcomes were caused by teacher centered learning, the use og monotonous lecture methods, and the lack of interactive learning media. As a result, studentswere less active, easily bored, unfocused, and had dificulties understanding map concepts such as symbols, legends, cardinal directions, and scales. This study aims to determine the implementation of the Problem-Based Learning (PBL) model through Wordwall learning media on the “recognizing maps” material in the IPAS subject for fourth-grade students at SDN Banjarsawah I, and to determine the improvement in learning outcomes through the application of the Problem-Based Learning (PBL) model using Wordwall learning media in the IPAS subject for fourth-grade students at SDN Banjarsawah I. This study used Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of planning, action implementation, observation, and reflection stages. The subjects of the study were 11 fourth-grade students of SDN Banjarsawah I, consisting of 5 male students and 6 female students. Data collection teachniques were carried out throught observation, interviews, tests, and documentation. The Minimum Completeness Criteria (KKM) determined was 70 with classical completeness of 80%. The results of the study indicated that the implementation of the Problem-Based Learning (PBL) model assisted by Wordwall learning media was able to improve students’ learning outcomes. In the pre-cycle stage, the students’ average score was only 65.63%, with a learning completeness percentage of 36.36%, meaning that only 4 students achieved mastery, while 7 students (63.63%) had not yet reached the Minimum Completeness Criteria (KKM). After the implementation of the action in Cycle I, the average score increased to 75.54%, with learning completeness reaching 54.54%, or 6 students achieving mastery, while 5 students (45.45%) were still incomplete. In Cycle II, students’ learning outcomes improved again, with the average score reaching 84.27 and learning completeness increasing to 81.81%, or 9 students achieving mastery, while 2 students (18.18%) had not yet reached the KKM. These two students were subsequently provided with reflection activities and special guidance by the teacher through learning assistance, motivational support, and additional exercises so that they could better understand the topic of map recognition and improve their learning outcomes. Furthermore, student activity in the learning process also increased from 56.52% in Cycle I to 75% in Cycle II. Therefore, the implementation of the PBL model assisted by Wordwall learning media proved to be effective in improving students’ learning outcomes on the topic of map recognition in Grade IV at SDN Banjarsawah I.